Penggunaan Styrofoam Sebagai Bahan Tambah Campuran AC-BC Menggunakan Batu Sungai Pucak Kabupaten Maros - Elthon Faraknimela; Mary Selintung; Alpius (Paulus Civil Engineering Journal, 2022)
Styrofoam is a type of plastic polymer that is thermoplastic in nature where if heated it will melt or become soft and harden or return to solid if cooled. Styrofoam is often found in several places, mainly in electronic store warehouses. The purpose of this study was to determine the effect of using styrofoam as an added ingredient in the AC-BC mixture using Pucak River stone. The initial stage of the study began with a series of tests of rough, fine, and filler characteristics and the designed the composition of the mixture for conventional Marshall Immersion and Marshall testing to obtain the Residual Marshall Stability value. This research was conducted and located in the Road and Asphalt Laboratory of Indonesia Paulus Makassar using levels of 0%, 0,5%, 1%, 1,5%, and 2% showed that the use of added materials in the AC-BC mixture was able to fill stabilitas, VIM, VMA, flow, and VFB and had met the specifications of the Directorate General of Wildlife Development 2018.